In situ fibrillation of polypropylene/polyamide 6 blends: Effect of organoclay addition. Issue 12 (5th December 2014) - Chomat, Dimitri; Soulestin, Jérémie; Lacrampe, Marie‐France; Sclavons, Michel; Krawczak, Patricia
ABSTRACT In situ fibrillation of PP/PA6 blends (85/15 wt %) is investigated in presence of two kinds of organically modified montmorillonite, differing by the polarity of their surfactant. The organoclay is primary dispersed either in the PP (for the low‐polarity Cloisite® 15A) or in the PA6 (for the high‐polarity Cloisite® 30B), according to its assumed affinity. In absence of organoclay, a fibrillar morphology is achieved after the melt‐blending and hot‐stretching step, as evidenced by SEM analysis. Upon clay addition, different morphological trends are evidenced. The C15A leads to a refinement of the fibrils whether the C30B induces a transition from fibrillar to nodular structure. These trends are ascribed to drastic changes in viscosity and elasticity ratios, due to the filler initial localization. Several techniques (DSC, STEM) point out a C15A migration from the PP to the PP/PA6 interface. Rheological measurements highlight the possibility of a double‐percolation phenomenon, linked to the fibrillar microstructure of the PP/PA6/C15A blend. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41680.